#MADRES. Parodic Motherhood Discourses on Peruvian TikTok - (:unkn) unknown (Taylor & Francis, 2024)
TikTok’s increasing cultural pervasiveness, leading to a myriad of practices and discourses, has turned the platform into a rich digital field site to interpret local dynamics. Here, we analyze visual and textual discourses on (urban) Peruvian TikTok a...
Keywords: Maternidad paródica; TikTok